Complete withdrawal is the most feasible treatment for medication‐overuse headache: A randomized controlled open‐label trial. (15th March 2019) - Engelstoft, Ida Maria Storm; Carlsen, Louise Ninett; Munksgaard, Signe Bruun; Nielsen, Mia; Jensen, Rigmor Højland; Bendtsen, Lars
Abstract: Background: Complete stop of acute medication and/or migraine medication for treatment of medication‐overuse headache (MOH) has previously been reported more effective in reducing headache days and migraine days per month compared with restricted intake of acute medication. However, it is unknown whether complete stop or restricted intake is the most feasible treatment for patients. Objectives: To investigate whether feasibility of withdrawal in MOH is different between complete stop of acute medication and restricted intake, and whether reductions in headache‐related medication dependence, anxiety and depression differ between the treatments. Methods: Medication‐overuse headache patients were included in a prospective, open‐label, outpatient study and randomized to two months of withdrawal with either no analgesics or acute migraine medication (programme A) or acute medication restricted to 2 days/week (programme B). After 6 and 12 months, patients graded feasibility of withdrawal. Dependence was measured by Severity of Dependence Scale (SDS), while anxiety and depression were measured by Hospital Anxiety and Depression Scale (HADS). Results: We included 72 MOH patients with primary migraine and/or tension‐type headache. Forty‐nine completed withdrawal and the SDS questionnaire at 12‐month follow‐up, and the feasibility of withdrawal was significantly higher in programme A compared to programme B ( p <  0.001). At 12 months, the dependence was reduced by 44% in programme A compared to 26% in programme B ( p  = 0.053), while the anxiety score was reduced by 32% and 11%, respectively ( p  = 0.048). Conclusions: Withdrawal with complete stop of acute medication was more feasible and most effective in reducing headache‐related anxiety compared with restricted intake. Significance: A c omplete stop of all analgesics is the most effective treatment for MOH regarding reduction in headache days but has often been regarded as too challenging for patients. However, in this study, complete stop appears to be more feasible compared with restricted intake of analgesics seen from the patients' perspective.